Laparoscopy-Assisted Distal Pancreatectomy - Hirota, Masahiko; Hashimoto, Daisuke; Sakata, Kazuya; Kuroki, Hideyuki; Tanaka, Youhei; Ishiko, Takatoshi; Motomura, Yu; Ishikawa, Shinji; Kiyota, Yoshitaka; Arita, Tetsumasa; Inayoshi, Atsushi; Yagi, Yasushi (IntechOpen, 2011)
None